2020
DOI: 10.1080/13696998.2020.1789866
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and lifetime hospital costs of patients suffering from wild-type transthyretin amyloid cardiomyopathy in Denmark

Abstract: Aims: Wild-type transthyretin amyloid cardiomyopathy (ATTRwt) is a fast progressing and fatal disease associated with substantial delays in diagnosis. Between the first symptoms and diagnosis, patients are frequently hospitalized, primarily with cardiac symptoms. After diagnosis, patients continue to experience frequent hospital admissions. The objective of this study was to estimate the Danish diagnostic and lifetime hospital costs associated with the treatment of patients with ATTRwt both before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This cycling through different investigations and services would be largely avoided with prompt diagnosis. An economic evaluation by Pilgaard et al of diagnostic and lifetime hospital costs of patients with ATTRwt-CM in the Danish healthcare setting concluded that healthcare resource use costs could be reduced through earlier diagnosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…This cycling through different investigations and services would be largely avoided with prompt diagnosis. An economic evaluation by Pilgaard et al of diagnostic and lifetime hospital costs of patients with ATTRwt-CM in the Danish healthcare setting concluded that healthcare resource use costs could be reduced through earlier diagnosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although the epidemiology of ATTR‐CM is beginning to emerge in published research using register data, 8,11–13 treatment patterns for ATTR‐CM patients and their healthcare resource use are not well documented. There is a large body of work on the humanistic and economic burden of heart failure from around the world, 14–16 but only few studies on the healthcare resource use of ATTR‐CM 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the epidemiology of ATTR‐CM is beginning to emerge in published research using register data, 8,11–13 treatment patterns for ATTR‐CM patients and their healthcare resource use are not well documented. There is a large body of work on the humanistic and economic burden of heart failure from around the world, 14–16 but only few studies on the healthcare resource use of ATTR‐CM 17–19 . Existing studies have been limited to modelled resource use based on data collected from peer‐reviewed journal articles, claims data covering only part of the country population, self‐reported resource use, and did not compare resource use of ATTR‐CM patients to that of a relevant population such as general HF patients not diagnosed with ATTR‐CM.…”
Section: Introductionmentioning
confidence: 99%
“…ATTRwt is a condition that is often underdiagnosed and misdiagnosed leading to diagnostic delay 2 6. As such, patients, their families and healthcare services may incur increased burden during extended contact associated with diagnostic investigations 22 27 28. Furthermore, delays in ATTRwt diagnosis are associated with more advanced disease at diagnosis 27 29.…”
Section: Discussionmentioning
confidence: 99%